2022
DOI: 10.3389/fcimb.2022.831186
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Related Inflammation Factors as a Potential Biomarker for Diagnosing Major Depressive Disorder

Abstract: ObjectiveAlthough many works have been done, the objectively measured diagnostic biomarkers are not available. Thus, we conducted this study to identify potential biomarkers for objectively diagnosing depression and explore the role of gut microbiota in the onset of depression.MethodsMajor depressive disorder (MDD) patients (n=56) and demographic data-matched healthy controls (HCs) (n=56) were included in this study. The gut microbiota in fecal samples and inflammation-related factors in serum were measured. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…The suffering caused by self-mutilation, suicide, and other behaviors of depression patients to patients and their families and the loss to society cannot be ignored ( 1 ). In the past few decades, researchers have sought breakthroughs in the diagnosis of depression, from relying solely on symptomatic diagnosis to the birth of various markers, such as blood biomarkers and molecular genetics biomarkers: BDNF Val66Met, 5-HTTLPR risk gene biomarkers, and gut microbiota ( 2 – 4 ). However, a simple and objectively effective diagnostic marker has not been found.…”
Section: Introductionmentioning
confidence: 99%
“…The suffering caused by self-mutilation, suicide, and other behaviors of depression patients to patients and their families and the loss to society cannot be ignored ( 1 ). In the past few decades, researchers have sought breakthroughs in the diagnosis of depression, from relying solely on symptomatic diagnosis to the birth of various markers, such as blood biomarkers and molecular genetics biomarkers: BDNF Val66Met, 5-HTTLPR risk gene biomarkers, and gut microbiota ( 2 – 4 ). However, a simple and objectively effective diagnostic marker has not been found.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that gut microbiota composition was significantly altered, particularly in the composition of Firmicutes , Actinobacteria , and Bacteroidetes at the phylum level in patients with major depressive disorder (MDD) and in mouse models [ 36 ]. In the social defeat stress (SDS) and chronic unpredictable mild stress (CUMS) mice [ 37 , 38 , 39 ] and clinic MDD patients [ 40 , 41 ] all showed that the substantially high correlation between the depression-like behaviors and gut microbiota composition, including from intestine and/or fecal samples. Their studies have shown an increased Firmicutes , Sutterella , Oscillospira , Bacteroidetes , Proteobacteria , Actinobacteria , and Verrucomicrobia abundance in intestines and/or fecal under depression-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, increased immune system activation has been associated with depression ( Bai, 2022 ). The homeostasis of the intestinal barrier immune defenses is critical in preventing the host from undergoing mood and cognitive changes due to bacterial influences ( Leclercq, 2012 ; Maes, 2012 ).…”
Section: Discussionmentioning
confidence: 99%